Development of microsatellite markers for Rhodiola rosea - Veress, A.; Lendvay, B.; Pedryc, A.; György, Z. (International Journal of Horticultural Science, 2015)
Rhodiola rosea L. is an important adaptogen medicinal plant. In this study two new microsatellite markers were developed. The assessment of the genetic diversity of R. rosea has recently started with molecular markers, but only a few species-specific microsatellite markers have been published so far. However the small number of markers allows only a limited insight into the genetic variability of the species therefore the aim of our work was to develop new microsatellite markers for R. rosea with a microsatellite enrichment library technique. Genomic DNA was cleaved with an endonuclease enzyme followed by adaptor ligation and PCR amplification. DNA fragments that contained microsatellites were first isolated using a biotin-streptavidin linkage based magnetic selection and then cloned into plasmids. Out of forty-three sequenced clones three contained microsatellites, in these cases primers were designed for the amplification of the microsatellite repeats. The newly developed primer pairs were tested on individuals from distant R. rosea populations and the variability of the amplified fragments was estimated by fragment-length analysis. The locus RhpB14a was found to be monomorphic while RhpB14b and RhpB13 were polymorphic. As a result of the present study, two novel variable microsatellite loci were identified in the genome of R. rosea.